2021
DOI: 10.1093/ibd/izab204
|View full text |Cite
|
Sign up to set email alerts
|

Oral Delivery of Encapsulated All-Trans Retinoic Acid Ameliorates Disease in Rodent Models of Colitis

Abstract: Background All-trans retinoic acid (ATRA) is a biologically active isomer of retinoic acid (RA). Topical ATRA (retin-a, retin-a micro, atralin, renova, and avita) is the active pharmaceutical ingredient for FDA-approved treatments for acne and skin wrinkles. Oral formulations (Vesanoid) treat acute promyelocytic leukemia, but oral dosing can induce severe side effects. Despite benefits in various rodent models of inflammatory bowel disease (IBD), toxicity and controversial clinical observatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…[ 19 ] RA is a key derivative of vitamin A, which has been considered to relieve colitis. [ 16 ] We found that L. intestinalis treatment elevated fecal RA levels in colitis mice, as well as in culture media inoculated with L. intestinalis ( Figure A; Figure S6A, Supporting Information). In addition, RA supplementation exerted an anti‐colitis effect (Figure 4B–D; Figure S6B–E, Supporting Information).…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…[ 19 ] RA is a key derivative of vitamin A, which has been considered to relieve colitis. [ 16 ] We found that L. intestinalis treatment elevated fecal RA levels in colitis mice, as well as in culture media inoculated with L. intestinalis ( Figure A; Figure S6A, Supporting Information). In addition, RA supplementation exerted an anti‐colitis effect (Figure 4B–D; Figure S6B–E, Supporting Information).…”
Section: Resultsmentioning
confidence: 96%
“…RA, an important derivative of vitamin A metabolism, has a therapeutic effect on UC according to several clinical and preclinical studies. [ 16,17 ] Here, we showed that L. intestinalis not only metabolized vitamin A via its intrinsically high ALDH activity, but also enhanced RA metabolism in the host intestine. Hence, co‐metabolism of L. intestinalis and the host contributes to increased RA biosynthesis in vivo, and L. intestinalis is a safe and effective probiotic in boosting the beneficial effect of vitamin A in UC treatment.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…It works by increasing cell turnover and reducing the formation of comedones (clogged pores) that reduce the formation of blackheads and whiteheads. Tretinoin is usually used in topical form under the brand name Retin‐A 61 . However, tretinoin can be irritating to the skin, which limits its effectiveness.…”
Section: Ethosomes Applications In Cosmetic Deliverymentioning
confidence: 99%
“…Tretinoin is usually used in topical form under the brand name Retin-A. 61 However, tretinoin can be irritating to the skin, which limits its effectiveness. By incorporating tretinoin into ethosomes, the drug can be delivered directly to the sebaceous glands, where it can target the underlying causes of acne, leading to improved efficacy and reduced side effects.…”
Section: Ethosomes For Acnesmentioning
confidence: 99%